2017
DOI: 10.7554/elife.23332
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal dysfunctions cause lysosomal storage and axonal Kv1 channel redistribution in peripheral neuropathy

Abstract: Impairment of peripheral nerve function is frequent in neurometabolic diseases, but mechanistically not well understood. Here, we report a novel disease mechanism and the finding that glial lipid metabolism is critical for axon function, independent of myelin itself. Surprisingly, nerves of Schwann cell-specific Pex5 mutant mice were unaltered regarding axon numbers, axonal calibers, and myelin sheath thickness by electron microscopy. In search for a molecular mechanism, we revealed enhanced abundance and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…It is also known that peroxisomal disorders are accompanied with cholesterol accumulation in lysosomes (8,9), demonstrating that peroxisome plays an important role in cholesterol transport from lysosome. Although the regulation of PIP4K2A is not well characterized, there are some clues suggesting PIP4K2A may be involved in LSD in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also known that peroxisomal disorders are accompanied with cholesterol accumulation in lysosomes (8,9), demonstrating that peroxisome plays an important role in cholesterol transport from lysosome. Although the regulation of PIP4K2A is not well characterized, there are some clues suggesting PIP4K2A may be involved in LSD in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of peroxisomal PI(4,5)P 2 results in cholesterol accumulation in lysosomes (8). Lysosome-peroxisome association is also observed in mouse neurons (9). Peroxisomal dysfunction caused expanded lysosomes likely due to impairment of the organelle contacts (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this mouse, axonopathy progression was halted and biochemical markers of oxidation and ER stress were ameliorated by antioxidant compound and TUCDA bile acid therapies. (Fourcade, Lopez-Erauskin, Ruiz, Ferrer, & Pujol, 2014;Launay et al, 2017;Lopez-Erauskin et al, 2011) In the peripheral nerves of the Abcd1 mouse, Kleinecke demonstrated lysosomal storage and increased VLCFA in gangliosides of lipid rafts causing altered axonal Kv1 channels in Schwann cells leading to peripheral neuropathy which was age dependent (Islinger et al, 2018;Kleinecke et al, 2017).…”
Section: Murine Modelsmentioning
confidence: 99%
“…In Schwann cells, the defect in ether lipid biosynthesis was demonstrated to impair the recruitment of AKT to the plasma membrane thereby inhibiting its proper phosphorylation, which in turn causes aberrant phosphorylation and overt activation of the downstream kinase glycogen synthase kinase (GSK) 3β and finally impaired myelin formation and maintenance . However, a recent study of mice with Schwann cell‐selective KO of Pex5 did not reveal such abnormalities in myelination suggesting that the inherent defect in Schwann cells is only one aspect of the myelination problem and that also interaction with other compartments (e.g., axons) with additional disturbances is involved in mice with global ether lipid deficiency. Another study found decreased phosphorylation of both AKT and ERK phosphorylation after injection of lentiviral shRNAs against the Gnpat mRNA into the cerebral cortex of mice ; while exogenous supplementation with plasmalogens in cultured neuronal cells was suggested to enhance AKT and ERK phosphorylation via the induction of G protein‐coupled receptors .…”
Section: Molecular Basis and Potential Mechanisms Underlying The Phenmentioning
confidence: 99%